The Salt Tolerance Related Protein (STRP) Mediates Cold Stress Responses and Abscisic Acid Signalling in Arabidopsis thaliana - Fiorillo, Anna; Mattei, Maurizio; Aducci, Patrizia; Visconti, Sabina; Camoni, Lorenzo (Frontiers in Plant Science, 2020)
Low temperature stress is one of the major causes of crop yield reduction in agriculture. The alteration of gene expression pattern and the accumulation of stress-related proteins are the main strategies activated by plants under this unfavourable condition. Here we characterize the Arabidopsis thaliana Salt Tolerance Related Protein (STRP). The protein rapidly accumulates under cold treatment, and this effect is not dependent on transcriptional activation of the STRP gene, but on the inhibition of proteasome-mediated degradation. Subcellular localization of STRP was determined by the transient expression of STRP-YFP in A. thaliana protoplasts. STRP is localized into the cytosol, nucleus, and associated to the plasma membrane. Under cold stress, the membrane-associated fraction decreases, while in the cytosol and in the nucleus STRP levels strongly increase. STRP has high similarity with WCI16, a wheat Late Embryogenesis Abundant (LEA)-like protein. Despite no canonical LEA motifs in the STRP sequence are present, physicochemical characterization demonstrated that STRP shares common features with LEA proteins, being a high hydrophilic unstructured protein, highly soluble after boiling and with cryoprotectant activity. To clarify the physiological function of STRP, we characterized the phenotype and the response to low temperature stress of the strp knockout mutant. The mutation causes an equal impairment of plant growth and development both in physiological and cold stress conditions. The strp mutant is more susceptible to oxidative damage respect to the wild type, showing increased lipid peroxidation and altered membrane integrity. Furthermore, the analysis of Abscisic acid (ABA) effects on protein levels and on plant growth and development demonstrated that the hormone induces the increase of the amount of STRP, an effect in part ascribable to its ability to activate STRP expression. ABA treatments showed that the strp mutant displays an ABA hyposensitive phenotype in terms of seed germination, root development, stomata closure and in the expression of ABA-responsive genes. In conclusion, our results demonstrate that STRP acts as a multifunctional protein in the response mechanisms to low temperature, suggesting a crucial role for this protein in stress perception and in the translation of extracellular stimuli in an intracellular response.